2006
DOI: 10.1007/s00249-006-0114-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of coagulation factor VIIa’s affinity for phospholipid membranes

Abstract: The interaction between the gamma-carboxyglutamic acid-rich domain of coagulation factor VIIa (FVIIa), a vitamin-K-dependent enzyme, and phospholipid membranes plays a major role in initiation of blood coagulation. However, despite a high sequence and structural similarity to the Gla domain of other vitamin-K-dependent enzymes with a high membrane affinity, its affinity for negatively charged phospholipids is poor. A few amino acid differences are responsible for this observation. Based on the X-ray structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…480 The GLA domain of coagulation factor VII (FVII-GLA) has also been studied using AA simulations, with SMD used to assess the rupture force of PS unbinding from wildtype and mutant FVII-GLA domains. 481 Ohkubo et al used SMD to simulate FVII-GLA binding to a 100% PS membrane, and later simulated spontaneous binding of the same domain to a PS-HMMM membrane. 176 This allowed for demonstration of hydrophobic keel binding to the membrane core, the importance of Ca 2+ ions in association of FVII-GLA with anionic lipids, and identification of protein residues with significant lipid contacts.…”
Section: Membrane-bound Enzymesmentioning
confidence: 99%
“…480 The GLA domain of coagulation factor VII (FVII-GLA) has also been studied using AA simulations, with SMD used to assess the rupture force of PS unbinding from wildtype and mutant FVII-GLA domains. 481 Ohkubo et al used SMD to simulate FVII-GLA binding to a 100% PS membrane, and later simulated spontaneous binding of the same domain to a PS-HMMM membrane. 176 This allowed for demonstration of hydrophobic keel binding to the membrane core, the importance of Ca 2+ ions in association of FVII-GLA with anionic lipids, and identification of protein residues with significant lipid contacts.…”
Section: Membrane-bound Enzymesmentioning
confidence: 99%
“…In the X-ray-and NMR-solved structures of the GLA domain of bovine prothrombin, charged side chains and Ca 2+ ions interact with a single molecule of 1-oleoyl-2-hydroxy-sn-glycero-3-phospho-L-serine (lysophosphatidylserine, or, in short, lysoPS) (Huang et al, 2003). Taboureau and Olsen (2007) carried out simulations to pull out the lysoPS from the complex and investigated the role of protein side chains in membrane binding. McCallum et al (1996) estimated the distance from the membrane to the active site in the protease domain of human FVIIa along the membrane normal to be about 76 A ẘhen FVIIa is associated with TF.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not detect any noticeable change in the overall secondary structure of FVIIa in the presence of soluble lipids from the CD spectroscopic measurement (data not shown). Notably, Taboureau et al also reported no perturbation in FVIIa due to the insertion of C6Lyso-PS [30]. Both single and two lipid titrations with des Gla-FVIIa revealed the fact that at least one of the two lipid binding sites exists in the Gla domain.…”
Section: Discussionmentioning
confidence: 94%
“…Lysolipids are an emerging class of signaling lipids involved in inflammatory and autoimmune diseases [28]. Activated platelets secrete Lyso-PS [29] and lyso-PE [30] in vitro. Lyso-PS may be involved specifically in platelet activation in vivo, [31] yet its physiological function has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%